2021
DOI: 10.1016/j.jaim.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characteristics from Phaleria macrocarpa and its inhibitory activity on the peritoneal damage of endometriosis

Abstract: Background Endometriois represents a gynecological disease that still becomes an issue in community. Phaleria macrocarpa is a plant native to Indonesia that contains an antioxidant substance, which may serve as apoptotic modulator and useful for angiogenesis. Objective This study aims to evaluate the effects of flavonoid isolates from P. macrocarpa (PM) on the development of granulomas, apoptosis, proliferation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
9
0
3
Order By: Relevance
“…Six flavonoid compounds of Phaleria macrocarpa fruit were retrieved from their three-dimensional structures in PubChem Database (https://pubchem.ncbi.nlm.nih.gov/). Those compounds were eriodictyol (CID 440735), glycitin (CID 187808), 5-O-methylgenistein (CID 5748551), catechin 7-O-beta-D-xyloside (CID 73533), 8prenylnaringenin (CID 480764), and naringenin (CID 932) [18]. Matrix metalloproteinase-1 (MMP1) as the targeted protein was taken out of the structure from Protein Data Bank with ID 1CGE [19].…”
Section: Structure Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…Six flavonoid compounds of Phaleria macrocarpa fruit were retrieved from their three-dimensional structures in PubChem Database (https://pubchem.ncbi.nlm.nih.gov/). Those compounds were eriodictyol (CID 440735), glycitin (CID 187808), 5-O-methylgenistein (CID 5748551), catechin 7-O-beta-D-xyloside (CID 73533), 8prenylnaringenin (CID 480764), and naringenin (CID 932) [18]. Matrix metalloproteinase-1 (MMP1) as the targeted protein was taken out of the structure from Protein Data Bank with ID 1CGE [19].…”
Section: Structure Retrievalmentioning
confidence: 99%
“…Phaleria macrocarpa was traditionally used for reducing cholesterol, atherosclerosis, and diabetes mellitus [14][15][16][17]. Our previous study revealed that Phaleria macrocarpa contained six flavonoids, including eriodictyol, glycitin, 5-O-methylgenistein, catechin 7-O-beta-D-xyloside, 8prenylnaringenin, and naringenin and inhibited peritoneal damage in the endometriosis mice model [18]. A flavonoids compound has been reported high activity to reduce cancer proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Sedangkan triterpenoid tidak ditemukan keberadaannya dalam ekstrak metanol buah mahkota dewa. Hasil ini berbeda dengan yang diteliti oleh Maharani et al (2021) yang menyebutkan bahwa ekstrak metanol buah mahkota dewa mengandung semua senyawa metabolit sekunder seperti alkaloid, steroid, triterpenoid, flavonoid, saponin dan tanin. Hal ini dipahami bahwa kandungan metabolit sekunder suatu tanaman juga dipengaruhi oleh lokasi penanaman dan umur tanaman, sehingga hasil uji fitokimia yang berbeda sangat dimungkinkan (melo et al 2022).…”
Section: Hasil Dan Pembahasanunclassified
“…Urutan nilai rendemen dan LC50 adalah F1 > F3 > F2. Berdasarkan Tabel 2 dapat disimpulkan bahwa ketiga fraksi bersifat toksik karena dapat mematikan 50% populasi larva udang pada konsentrasi kurang dari 1000 ppm (Maharani et al 2021), dengan demikian F2 lebih bersifat toksik dibandingkan F3 dan F1 (F2 > F3 > F1). Apabila dilihat lebih lanjut maka terdapat korelasi positif antara rendemen fraksi dengan tingkat toksisitas yang berarti semakin kecil rendemen hasil fraksinasi kolom akan menghasilkan nilai toksisitas yang kecil.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation